Jammed joints and constricted heart: The science of tribology and missing lubricin. A case report on camptodactyly-arthropathy-coxa vara-pericarditis syndrome - Krishnan Ganapathy Subramaniam; Satish Mohanty; Dhruva Sharma; Komal Tamildasan; Narahari Srinath Reddy (Wolters Kluwer Medknow Publications, 2024)
An autosomal recessively inherited noninflammatory arthropathy known as camptodactyly, arthropathy, coxa vara, and pericarditis (CACP) syndrome was discovered in 1999. It is distinguished by synoviocyte hyperplasia and subcapsular fibrosis of the synovial capsule, which results in a shortage of lubricin production. The resulting lack of joint lubrication induces increased mechanical stress, causing progressive deformities that become evident with weight-bearing and heightened joint activity. Animal models with a lubricin gene knock-out display similar traits, underscoring the impact of mechanical stress on disrupting type II collagen on the articular surface. The gradual development of pericarditis and constriction often results in misdiagnosis as juvenile rheumatoid arthritis with cardiac involvement, but the defining feature remains the noninflammatory nature of the disease. Early recognition is pivotal, as interventions such as pericardiectomy and recombinant human lubricin hold promise for altering the disease's natural course. In our familial case of CACP, two siblings exhibited distinct phenotypic variations - one with fibrosis-dominant features and pericardial constriction and the other displaying synovial hyperplasia without pericardial involvement.